Characterization of Cu(II)-ACC Complexes and Conversion of the Bound ACC into Ethylene in the Presence of Hydrogen Peroxide. Detection of a Brown Intermediate at Low Temperature - Wadih Ghattas; Michel Giorgi; Christian Gaudin; Antal Rockenbauer; Marius Réglier; A. Jalila Simaan (Bioinorganic Chemistry and Applications)
Two copper(II)-ACC complexes were prepared and characterized: [Cu(bpy)(ACC)(H2O)]⋅CO4 (1) and [Cu(ACC)2]3⋅4H2O (2). Their crystallographic structures are described and analyzed. Spectroscopic characterizations (UV-visible and EPR) confirm that the structure is maintained in solution. These complexes are able to produce ethylene in the presence of hydrogen peroxide in an “ACC Oxidase-like” reaction in water and in methanol. The conversion of ACC into ethylene depends on the amount of base, and, in methanol, 3 equivalents of NaOH are needed for optimum activity. The base is proposed to play a role in H2O2 deprotonation. The presence of an exogenic ligand (bpy) is important for the reactivity and may stabilize a reaction intermediate. Indeed, a brown intermediate with an absorption band centered at 433 nm can be detected at low temperature when 1 is treated with 10 equivalents of H2O2.